Studies on Population Dynamics of Fisheries of Goa Coast - Kulkarni Rajender Rao; Ruchika R. Dessai; Juliana Silveira (New Visions in Biological Science Vol. 5, 2021)
The population dynamic resources are among the most significant parts in fisheries science. The methods in which a population increases or decreases over time, as a result of births, deaths, immigration and emigration are explained by population dynamics. It serves as the foundation for understanding changing population diversity patterns as well as issues such as habitat destruction, predation and optimal harvesting rates. The goal of this study was to look into the population dynamics of economically important fish species along the Goa coast. Preliminary Data was gathered from the web site for stock assessments, which provide information about the availability of resources and are critical for management, since they also include information on mortality from fishing, interactions with other species and environmental factors. The data in this study came from 15 different fish species, with mackerel, tuna, and sardines being among the most popular. However, Chirocentrus dorab (silver bar) had the highest growth rate of 0.188340, while Sardinella longiceps (sardines) had the lowest rate 0.00003392.